Risk Assessment for Pulmonary Artery Hypertension in Adult Patient with Uncorrected Atrial Septal Defect by Six-Minute Walk Test and Mean Pulmonary Arterial Pressure - Suryantoro M., et al (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Risk Assessment for Pulmonary Artery Hypertension in Adult Patient with Uncorrected Atrial Septal Defect by Six-Minute Walk Test and Mean Pulmonary Arterial Pressure